(untitled) (Bangladesh Journal of Animal Science, 2016)
The study was conducted to investigate the phenotypic features, morphometry and production potentialities of indigenous dwarf chicken (IDC) of Bangladesh under intensive management condition. A total of 48 females and 12 males were collected from different districts and the experiment was performed at BAU Poultry farm for a period of 75 weeks. The predominant plumage and skin color were black and white, respectively. The average shank length, shank circumference and live weight (28 weeks) in adult males and females were 7.5 and 4.69 cm, 6.28 and 3.69 cm, and 1.77±0.38 and 1.10±0.077 kg, respectively. The reduction of live weight for dwarf male and female chickens relative to their normal shanked counterparts (NSC) at same age was 12.91 and 16.91%, respectively. Hen day egg production, average egg weight, average feed intake and FCR (feed conversion ratio) of IDC were recorded 37.43%, 38.25 g, 69.57g and 4.58, respectively. The average age and weight at sexual maturity were recorded as 166.53 days and 1093 g, respectively. IDC consumed 11.13% less feed than NSC during 1-20 weeks. Survivability of IDC up to 0-8, 1-23 and 24-75 weeks of age were found 97.25, 94.90 and 95.24%, respectively. The study reveal that IDC had relatively lower adult weight and consumed less feed without affecting egg production compared to NSC under intensive management condition and could be exploited its potentiality for development of mini layer under semi-scavenging system of Bangladesh. Bang. J. Anim. Sci. 2016. 45 (1): 52-61